Individual specialization to non-optimal hosts in a polyphagous marine invertebrate herbivore. - Finn A Baumgartner; Henrik Pavia; Gunilla B Toth (PLoS ONE, 2014)
Factors determining the degree of dietary generalism versus specialism are central in ecology. Species that are generalists at the population level may in fact be composed of specialized individuals. The optimal diet theory assumes that individuals choose diets that maximize fitness, and individual specialization may occur if individuals' ability to locate, recognize, and handle different food types differ. We investigate if individuals of the marine herbivorous slug Elysia viridis, which co-occur at different densities on several green macroalgal species in the field, are specialized to different algal hosts. Individual slugs were collected from three original algal host species (Cladophora sericea, Cladophora rupestris and Codium fragile) in the field, and short-term habitat choice and consumption, as well as long-term growth (proxy for fitness), on four algal diet species (the original algal host species and Chaetomorpha melagonium) were studied in laboratory experiments. Nutritional (protein, nitrogen, and carbon content) and morphological (dry weight, and cell/utricle volume) algal traits were also measured to investigate if they correlated with the growth value of the different algal diets. E. viridis individuals tended to choose and consume algal species that were similar to their original algal host. Long-term growth of E. viridis, however, was mostly independent of original algal host, as all individuals reached a larger size on the non-host C. melagonium. E. viridis growth was positively correlated to algal cell/utricle volume but not to any of the other measured algal traits. Because E. viridis feeds by piercing individual algal cells, the results indicate that slugs may receive more cytoplasm, and thus more energy per unit time, on algal species with large cells/utricles. We conclude that E. viridis individuals are specialized on different hosts, but host choice in natural E. viridis populations is not determined by the energetic value of seaweed diets as predicted by the ODT.